2018
DOI: 10.1002/mc.22794
|View full text |Cite
|
Sign up to set email alerts
|

Decreased SCIN expression, associated with promoter methylation, is a valuable predictor for prognosis in acute myeloid leukemia

Abstract: The present study was aimed to investigate SCIN expression as well as promoter methylation and further explore their clinical relevance in acute myeloid leukemia (AML) patients. Real-time quantitative PCR was carried out to detect the expression level of SCIN in 119 AML patients and 37 healthy controls. Real-time quantitative methylation-specific PCR and bisulfite sequencing PCR were carried out to detect SCIN promoter methylation levels in 103 AML patients and 29 controls. As compared with controls, the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…1F). Notably, low SCIN expression is associated with an adverse AML prognosis 34 . Two other genes of interest for which expression also correlates with a DHS at nearby ERVs are TPD52 and AHSP, whose overexpression in AML is predictive of poor and favourable outcomes, respectively 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…1F). Notably, low SCIN expression is associated with an adverse AML prognosis 34 . Two other genes of interest for which expression also correlates with a DHS at nearby ERVs are TPD52 and AHSP, whose overexpression in AML is predictive of poor and favourable outcomes, respectively 35,36 .…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, we found ERVs with strong supporting evidence for their regulatory activity, as the expression levels of their vicinity genes were >4-fold higher in AML samples with DHS at a given ERV, versus those without ( Figure 1E). This included a strict correlation between chromatin accessibility at a LTR12C element and the expression of the SCIN gene ( Figure 1F), which has a mild predictive value for AML prognosis (Z.-H. Zhang et al, 2018). TPD52 and AHSP expression, which were correlated with the presence of DHS at a LTR12C and LTR5B element respectively, have also been linked to AML prognosis (Ha et al, 2019;Zhu et al, 2017).…”
Section: A-dar Chromatin Status Correlates With Nearby Gene Expressionmentioning
confidence: 96%
“…In this study, we finalized the relevant gene "KRT23 ULBP2 ASRGL1 SERPINA1 SCIN SLC28A2" that may affect Th-17 cells immune infiltration in COAD patients. We have now found that these genes are involved in the development of many diseases (42)(43)(44)(45)(46)(47)(48)(49),In non-gastrointestinal tumors, ASRGL1 has shown a high correlation in the prognosis of patients with locally advanced lymph node-negative prostate cancer and cervical cancer (42,50); SLC28A2 helps increase the role of ribavirin (RBV) in the treatment of viral hepatitis Hyperuricemia (HUA) has been implicated (48,51). KRT23 was identified as a specifically expressed gene in colorectal cancer and highly expressed in colorectal cancer (45).…”
Section: Discussionmentioning
confidence: 99%